Optimization of periprosthetic culture for diagnosis of Propionibacterium acnes prosthetic joint infection - Butler-Wu, Susan M; Burns, Erica M; Pottinger, Paul S; Magaret, Amalia S; Rakeman, Jennifer L; Matsen, 3rd, Frederick A; Cookson, Brad T (Journal of clinical microbiology, 2011)
Propionibacterium acnes is increasingly recognized as an important agent of prosthetic joint infection (PJI). However, the optimum culture conditions for recovery of this organism from PJI specimens have not been determined. By applying a prolonged 28-day culture incubation to all periprosthetic specimens received for bacterial culture from 198 revision arthroplasty procedures, we retrospectively determined that a 13-day culture incubation period is necessary for the recovery of P. acnes from patients with PJI. Incubation beyond this period was associated with increasing recovery of nondiagnostic isolates: 21.7% of P. acnes isolates believed to be clinically unimportant were recovered after 13 days of incubation. Importantly, a diagnosis of P. acnes PJI would have been missed in 29.4% of patients had extended culture incubation been applied only to anaerobic culture media. Although specimens from P. acnes PJIs were more commonly associated with the presence of ≥ 2 culture media positive for growth, acute inflammation (≥ 5 neutrophils/high-power field) was observed in only 40% of patients with PJIs that had more than one specimen submitted for bacterial culture. These results support the need for a minimum culture incubation period of 13 days to be applied to both aerobic and anaerobic culture media for all periprosthetic specimens. Optimal recovery of infecting organisms from PJI specimens will be an important component in generating a universal definition for PJI due to indolent agents of infection, such as P. acnes.